Fraudulent Financial Statement Detection Based on Hexagen Fraud Theory (Study on Banking Registered in IDX Period 2015 - 2019) - Selvi Novita Fouziah; Suratno Suratno; Syahril Djaddang (Budapest International Research and Critics University, 2022)
This study was to examine the relationship between Hexagon Fraud consisting of financial stability, external pressure, nature of industry, ineffective monitoring, TATA, CEO education, managerial ownership, and state owned entreprise to fraudulent financial statements with audit committees as moderation. The sample in this study as many as 28 companies and 100 units of analysis taken based on purposive sampling techniques from all banks listed on IDX in 2015-2019. This study uses the Moderated Regression Analysis (MRA) method with the SPSS 25 analysis tool.The results showed that the financial stability, managerial ownership, and state owned entreprise relevant to detecting fraudulent financial statement. In addition, the variable audit committee is able to moderate variable external pressure and managerial ownership against fraudulent financial statements. While other factors consisting of external pressure, nature of industry, ineffective monitoring, TATA, and CEO Education are irrelevant in detecting fraudulent financial statement.